Coupled level-set and immersed-boundary method for simulation of filling in a complex geometry based mold. (2nd December 2018) - Thakkar, Nihar; Lakdawala, Absar; Sharma, Atul; Karagadde, Shyamprasad
Abstract: A coupled level-set and immersed-boundary-method (CLSIBM) is proposed for simulation of liquid and gas phase flow during filling of a complex geometry based mold using a modified cut-cell technique. The CLSIBM uses Cartesian computational domain, with two level-set functions:ϕ f 1, f 2 for liquid-metal and gas interface and ϕf, s for liquid-metal/gas and solid (mold box) interface. The cut-cell based immersed boundary method enable us to handle any internal two-phase flow in complex geometry using a Cartesian grid. Numerical results are presented for filling in four different tanks/molds, demonstrating the robustness of the proposed method during mold filling in complex geometry mold box.